The Level of Coordination Thinking Among Mathematics Department Students And Their Ability To Solve Mathematical Problems In The Mathematical Analysis Subject (Journal of the College of Basic Education, 2024)
The current research aims to identify “the extent to which mathematics department students possess the levels of coordination thinking and their ability to solve mathematical problems.”To achieve the goal, the researcher used the descriptive approach and two tests were prepared to measure coordination thinking, consisting of (20) A paragraph distributed over coordination thinking skills, which include: (identifying attributes or qualities, identifying properties, parts of observation and relating relationships, differentiating between similar and different, comparing and contrasting, grouping and classifying, classification, seeing relationships and finding patterns, building a standard Arranging, setting priorities, making sequences, guessing, determining cause and effect), and a test to determine students’ ability to solve mathematical problems, which consisted of (20) items distributed to all mathematical problem-solving skills. “The skill of understanding the problem - the skill of planning the solution - the skill of implementing the solution - the skill “Verifying the Validity of the Solution” The researcher verified the validity of each type of test with a reliability of (0.82) for coordination thinking and (0.80) for solving mathematical problems and after applying the test to the sample consisting of (124) male and female students from the third stage - Department of Mathematics - College of Education Basic data processing and statistical analysis. The researcher reached the following results:1- The students of the third stage possess coordination thinking to a good degree.2- Third stage students have the ability to solve mathematical problems to a good degree